Role of Peritoneal Macrophages in Cytomegalovirus-induced Acceleration of Autoimmune Diabetes in BB-rats - Jan-Luuk Hillebrands; Nienke van der Werf; Flip A. Klatter; Cathrien A. Bruggeman; Jan Rozing (Clinical and Developmental Immunology)
Background: As one of the natural perturbants, infection with cytomegalovirus (CMV) is believed to play a role in the development of Type I diabetes. Using the DP-BB rat model for autoimmune diabetes, we here report about possible mechanisms responsible for R(at)CMV-induced accelerated onset of diabetes.